Computerized space flight planning - Brown, Craig Matthew, author; Thayer, Sanford B., advisor; Boes, Duane C., committee member; Duff, William S., committee member (Colorado State University. Libraries, 1973)
This thesis analyses manual and computerized techniques of preparing timelines of crew activities and orbital parameters in support of the NASA Skylab program. A brief discussion of timelines and their use in mission analysis is provided. Procedures used in both the manual and computerized generation of mission timelines are discussed and computer programs provided. Early program evaluation and current hardware requirements are discussed as they relate to the timeline generation task. An indepth cost-effectiveness study of flight planning alternatives is conducted to establish the superiority of one of the alternatives in meeting cost-effectiveness goals. Cost and effectiveness parameters are created and used in the analysis as a means of quantitatively measuring each alternatives cost-effectiveness. Engineering economy procedures for calculating a rate of return are applied to the computerized alternative and the results analyzed. Finally, an overall systems cost-effectiveness relative value of merit is established for each alternative using a ratio cost-effectiveness model. This value of merit is then used to establish the cost-effectiveness superiority of one of the alternatives. Conclusions about the alternatives are then drawn from the analyses and recommendations made as to their implementation for Skylab mission analysis.
Keywords: Space flight -- Data processing